Toulouse, le Mirail: a influência da cultura magrebina na apropriação do habitat em Bellefontaine - Mickael Gonçalves Rodrigues (2012)
The purpose of this thesis is to determine relationships betweenMaghrebians culture and appropriations of the habitat performed by residents of Bellefontaine, in Toulouse - Le Mirail. Being the population mainly native from countries of North Africa, this neighborhoodbecomes the scene of recompositions, destructions and reconstructions of the culture of origin of the inhabitants, which are fermented or otherwisedelayed by the elements that constitute this habitat. To answer thisquestion, the habitat was divided into three levels of analysis. The firstlevel is related to the neighborhood and refers to the transformation and appropriations of streets, public spaces etc. The second refers to theoutside space, near buildings. The former level is related to common gardens of residents living in the same building, entrance lobbies and access corridors. The third and final level of analysis is the house itself, where ownership is reached in its greatest extent. This analysiswas conducted through several methods. Objective observations of reality made over several days helped to understand the transformationsof various scales of the habitat through time. Participation in several neighborhood meetings allowed to question directly the inhabitants regarding the subjects of this work. The participation in two sessions thatgathered residents, architects and managers of the municipalities gived the possibility of hearing the point of views of both residents and architects concerning the finalized or ongoing projects in Bellefontaine. The influence exercised by residents in the several levels of the habitat - and vice versa - is mainly concentrated on the sexualization of space. TheMaghrebian culture dictates rules of conduct and behaviors inherent toeach gender, which are followed by local residents, and occasionally lead to a confrontation with the idealized vision of architects and urbanists. Tothe former, a better understanding of this culture would introduce newelements to projects, which could improve the way of living of allresidents.